Roux-en-Y gastric bypass vs sleeve gastrectomy in super obesity: a systematic review and meta-analysis - Gomes-Rocha, Sofia Raquel (2021)
© The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2021